PENGARUH PRODUCT BUNDLING DAN PRICE BUNDLING TERHADAP KEPUTUSAN MENGINAP DI D’BATOE BOUTIQUE HOTEL BANDUNG (Survei terhadap Tamu Individu yang Menginap di D’Batoe Boutique Hotel Bandung) - Dwi MD, Vitri; Gaffar, Vanessa; Novalita, Dewi Pancawati (THE Journal : Tourism and Hospitality Essentials Journal, 2014)
Decrease of D’Batoe Boutique Hotel’s room occupancy that continue happen from 2011 until 2013 makes hotel management find ways to increase room occupancy’s back, one of them is by increasing the decision to stay. One way that is used is performing product bundling and price bundling. The purpose of this research was to obtain discovery regarding product bundling, price bundling, the decision to stay as well as the effect of product bundling and price bundling to the decision to stay. The research used is descriptive verification, the sampling technique is cluster random sampling, as well as the number of samples 102 individual guests who stayed at D'Batoe Boutique Hotel. Techniques of data analysis and hypothesis testing used is multiple regression. The results showed that the product bundling, price bundling and the decision to stay has a high enough response. The most influential factors is the suitability of the price bundling package and bonuses offered. The weakest factor is the suitability of the price package offered by D'Batoe Boutique Hotel as a 3 star boutique hotel. Suggested to the hotel is to maintain and / or improve the product bundling strategy and price bundling with more attention and improve indikator that are still considered low by guests.